Liverwort flora of Ayan – a gained link between subarctic and hemiboreal floras in West Okhotiya (Pacific Russia) - Vadim Bakalin; Ksenia Klimova; Daniil Bakalin; Seung Se Choi (Biodiversity Data Journal, 2021)
The liverwort flora of Ayan was first investigated one hundred and fifty years after the first exploration of vascular plants. A number of factors has determined the relatively high taxonomic diversity of liverworts in this hemiarctic flora of small-sized area: 118 species and one subspecies were revealed. These data are new not only for the studied area, but also for the huge land adjacent to the western coast of the Sea of Okhotsk. The liverwort flora possesses the domination of taxa common in the hemiarctic, although with a lot of taxa more common in boreal as well as arctic-alpine environments. The presence of Mega-Beringian and calciphilous taxa is the peculiar trait of the studied liverwort flora. Based on detrended correspondence analysis (DCA), Ayan liverwort flora shows relationships to the continental mainland floras situated both in North-East Asian hemiarctic and hemiboreal East Asia and is, therefore, the link between both. The flora of Ayan surroundings is one of the newly-filled ‘blank spots’ in the possible floral exchange way between Arctic Northeast Asia and mountainous floras of temperate East Asia.